Indirect cathodic-stripping voltammetric determination of ceftazidime as a mercury salt - Ferreira, V. S.; Zanoni, Maria Valnice Boldrin [UNESP]; Fogg, A. G. (Elsevier B.V., 1998)
At accumulation potentials close to +0.1 V at a hanging mercury drop electrode, ceftazidime is accumulated at pH 9.5, probably in a hydrolysed or otherwise chemically altered form, in an anodic process to give an adsorbed mercury salt. The accumulation of this mercury salt allows the indirect cathodic-stripping voltammetric determination of ceftazidime using the reduction peak of the mercury salt at -0.70 V. The high sensitivity of the method coupled with high sample dilution allows ceftazidime to be determined in milk samples at the 28 mu g ml(-1) level without prior separation. In order to determine lower levels of ceftazidime in milk (ca. 10 ng ml(-1)) a separation process would be required. (C) 1998 Elsevier B.V. B.V. All rights reserved.
Keywords: ceftazidime; cathodic-stripping voltammetry; milk; mercury salt